MAKING FATWA IN POPULAR ISLAMIC INSTAGRAM ACCOUNT IN INDONESIA: PLANNING, PRODUCTION, AND AUDIENCE FEEDBACK - Aida Humaira; Hengki Ferdiansyah; Muhamad Masrur Irsyadi; Nurul Adhha; Unaesah Rahmah (al-Balagh : Jurnal Dakwah dan Komunikasi, 2022)
This study uses a production organization perspective on the process of creating content in the form of fatwas on Instagram accounts in Indonesia. During the rise of “online muftīs” through various social media platforms, this study describes the process of producing and disseminating fatwa content published by “online muftīs” on islami.co, bincangsyariah.com, and rumasyho.com. This research combines field research methods and content analysis as analytical methods. In the research, the writer acts as a follower to observe, reconstruct dialogue, describe, and document information and activities virtually. Then the results of the analysis are described descriptively. This study concludes that the creation of digital content in the form of online fatwas released by islami.co, rumaysho.com, and bincangsyariah.com on Instagram is motivated by several factors, namely the manager’s background, methodology for taking fatwas, and questions asked by followers in the media. social. The leaders and editors of the three media outlets issue fatwas by adapting, simplifying, and restating existing ulema’s fatwas to be published on social media in the form of short videos or infographics.